IMPACT OF IMPLEMENTATION OF TOTAL QUALITY MANAGEMENT: AN ASSESSMENT OF THE SAUDI INDUSTRY - Abd-Elwahed, Mohamed Salah; El-Baz, Mohamed Adel (The South African Journal of Industrial Engineering, 2018)
The main objective of this research is to measure the level of knowledge, understanding, and implementation of quality management tools in a sample of the industrial sector in Saudi Arabia, and to monitor the different policies to implement the quality strategies and the extent of their integration into the industrial management systems in general. A questionnaire to cover key elements, including knowledge and understanding of the various quality management (QM) approaches and the accompanying tools, is implemented. The impact of using each QM approach on the level of actual growth of the industrial organisations is verified, along with the impact of the executive method of management and its compatibility with the proper implementation of quality tools. The results of the study indicate that different visions of QM strategies and policies are still adopted by industrial companies participating in the survey. In addition, there is a difference in the levels of understanding and implementation of QM tools and techniques.